FUNDAMENTAL CHANGES OF INTERNATIONAL ECONOMIC LAW: CHALLENGES TOWARD LEGAL SYSTEM BASED ON FAIRNESS AND HUMAN VALUES - Warrouw, Adolf (UI Scholars Hub, 2021)
Economic globalization supported by the latest technology information and communication has brought major influence in the structure and substance of international law development. Such globalization leads to market integration, transportation system, and communication, which makes possible to companies, states, and individual to reach the world. This article explains on the fundamental challenges of international economic law to legal system based on fairness and human values.